The impact of new borders on trade: World War I and the economic disintegration of Central Europe - Hans Christian Heinemeyer (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2006)
This paper investigates the impact of changes in national border demarcation on economic integration. It treats the national breakups in Central Europe due to WWI as a natural experiment, which allows for evaluating the particular effect of new national borders. A gravity model of trade is used to analyze goods-specific trade among Central European regions. The main results are, first, that the treatment effect of new borders is large. Second, decomposing the border effect provides evidence of a 'border before border' for parts of Germany that became separated even before WWI. Third, the analysis indicates a high level of economic integration before WWI among Polish regions that became politically unified only after the war.
Keywords: 330